The parliamentary political agenda : a tool for policy analysis of diabetes priorities in Spain (2012)
ABSTRACT: Objective: To analyze the political agenda on diabetes in Spain under democracy by considering the frequency and content of initiatives in the Spanish parliament. Methods: A systematic search of parliamentary interventions (1979-2010) reported on the Spanish Congress of Deputies’ web page was carried out using the key word “diabetes”. A descriptive study of the frequency of interventions was performed, followed by a content analysis, according to the priorities of the World Health Organization (WHO), the International Diabetes Federation and the Spanish Diabetes Federation. Other study variables were the year of presentation, legislature, type of initiative and whether a political decision was taken (yes/no). Results: There were 59 interventions: 22% were related to the first international initiatives and 44.1% took place in the last two legislatures in response to the WHO’s program Diabetes Action Now. A total of 32.2% of the initiatives addressed educational and social programs, while 23.7% addressed access to resources and health services. Most initiatives (74.6%) consisted of parliamentary questions to the government, which only required a response. Of the 15 initiatives requiring a decision to be taken, only eight were approved. Conclusions: Spanish legislators aim to comply with international standards. Nevertheless, political decision-making has sometimes been slow. Importantly, most of the political responsibilities related to health have been transferred to the autonomous regions. The updated National Diabetes Strategy in Spain will need to strengthen public health policies according to established international priorities. Monitoring parliamentary interventions has proven to be a valid tool for evaluating patterns of political debate and decisions on diabetes.